Cryogenic electrolytes - Nazin, S.; Chikina, I.; Shikin, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The emphasis is made on experimentally observed indications of the presence of metastable ion dipoles in solid helium. Similar quasiparticles possessing positive scattering length for injected electrons are assumed to exist in liquid phases of cryogenic liquids. The observed phenomena allowing to detect and monitor the behavior of dipole gas in superfluid helium (referred to as cryogenic electrolyte) are discussed. Most interesting among these phenomena are: special features of the dielectric behavior of ion dipole gas, details of the temperature dependence of the ion dipole gas osmotic pressure at the boundary of the liquid 3He–4He solution stratification, relaxation phenomena of collective origin in cryogenic electrolytes, and liquid helium phonon spectrum transformation due to strong interaction between phonons and heavy dipole quasiparticles.